Taxonomy of Aonidiella yehudithae sp. nov. and Lindingaspis misrae (Laing) comb. nov. with a key to species of Aonidiella Berlese & Leonardi (Hemiptera: Coccoidea: Diaspididae) - Ben-Dov, Yair (Zootaxa, 2006)
Aonidiella yehudithae sp. nov. is described from ivy, Hedera helix collected on the island of Crete, Greece. Aonidiella misrae Laing, 1929 is transferred to Lindingaspis, a lectotype is designated, and the species is shown to be the senior synonym of Lindingaspis fusca McKenzie, 1943. A key is given for the separation of the 32 species currently included in the genus Aonidiella, based on the adult female.